Pengaruh Control Test Terhadap Ketepatan Tingkat Pengambilan Keputusan Akuntan Publik Dalam Menyatakan Opini di Kantor Akuntan Publik Surakarta dan Jogjakarta - Mulyadi . (Universitas Muhammadiyah Ponorogo, 2017)
The purpose of this study was to see how the influence of Structure of Internal Control which includes authorization of transactions and activities were adequate, the separation of functions and duties, the design and use of documents and records adequate, secure assets and adequate records, as well as the examination independent of the performance of the level the accuracy of decision-making Public Accountant in determining the audit opinion. Analysis techniques used in this research is the analysis of data validity, realiabilitas and hypothesis testing that includes testing multiple linear regression analysis, t-test, f and determination test. T test results is a positive effect and does not significantly. Authorization transaction F-test, is a positive effect and significanlty. Test results showed that the variables R2 Authorization transaction, Separation of Duties and activities were adequate, the use of documents and records adequate, Sentry asset and independent checks on performance are able to explain 12.9% of the variable precision of giving opinions by public accountants, while the rest of 87 , 1% is influenced by other variables.